Ability of observer and self-report measures to capture shared decision-making in clinical practice in the UK: a mixed-methods study. Issue 8 (17th August 2019) - Williams, Denitza; Edwards, Adrian; Wood, Fiona; Lloyd, Amy; Brain, Kate; Thomas, Nerys; Prichard, Alison; Goodland, Annwen; Sweetland, Helen; McGarrigle, Helen; Hill, Gwenllian; Joseph-Williams, Natalie
Abstract : Objectives: To examine how observer and self-report measures of shared decision-making (SDM) evaluate the decision-making activities that patients and clinicians undertake in routine consultations. Design: Multi-method study using observational and self-reported measures of SDM and qualitative analysis. Setting: Breast care and predialysis teams who had already implemented SDM. Participants: Breast care consultants, clinical nurse specialists and patients who were making decisions about treatment for early-stage breast cancer. Predialysis clinical nurse specialists and patients who needed to make dialysis treatment decisions. Methods: Consultations were audio recorded, transcribed and thematically analysed. SDM was measured using Observer OPTION-5 and a dyadic SureScore self-reported measure. Results: Twenty-two breast and 21 renal consultations were analysed. SureScore indicated that clinicians and patients felt SDM was occurring, but scores showed ceiling effects for most participants, making differentiation difficult. There was mismatch between SureScore and OPTION-5 score data, the latter showing that each consultation lacked at least some elements of SDM. Highest scoring items using OPTION-5 were 'incorporating patient preferences into decisions' for the breast team (mean 18.5, range 12.5–20, SD 2.39) and 'eliciting patient preferences to options' for the renal team (mean 16.15, range 10–20, SD 3.48). Thematic analysis identified that the SDM encounter is difficult to measure because decision-making is often distributed across encounters and time, with multiple people, it is contextually adapted and can involve multiple decisions. Conclusions: Self-reported measures can broadly indicate satisfaction with SDM, but do not tell us about the quality of the interaction and are unlikely to capture the multi-staged nature of the SDM process. Observational measures provide an indication of the extent to which elements of SDM are present in the observed consultation, but cannot explain why some elements might not be present or scored lower. Findings are important when considering measuring SDM in practice.